Petrographic analysis of Pre-Columbian pottery from four islands in the Lesser Antilles and implications for inter-island transport and interactions. (October 2016) - Lawrence, John A.; Marsaglia, Kathleen M.; Fitzpatrick, Scott M.
Abstract: Prehistoric Amerindian groups in the Lesser Antilles Island chain of the Caribbean used local materials for temper in the manufacturing of pottery and in some cases likely transported that pottery to other islands. To help better define possible cases of exchange, spheres of interaction, and population movements, we petrographically characterized temper in 93 thin sections of ceramic sherds from Pre-Columbian sites on the islands of Barbados (23), Mustique (32), and Union (13), as well as nine thin sections of local beach sand from Mustique that may have been used for tempering ceramics. An additional 25 thin sections of sherds from older (ca. 400–900 CE) occupation layers at the Grand Bay site were analyzed to complement the prior work. Based on petrographic description, the sherds were categorized into temper categories, many previously defined, but some newly delineated in this study. For more precise comparison, representative samples from each temper type were point-counted using the Gazzi-Dickinson method and their detrital modes plotted on various ternary diagrams. The Carriacou sherds include four temper types, three previously defined ( Placer, Igneous Volcaniclastic, Igneous Feldspathic) and a new Mixed temper type. The Union sherds have only Mixed and Igneous Volcaniclastic tempers. The Mustique sherds include three new temper types: Altered-Feldspathic, Altered-Silica and Altered-Epidote . The Barbados sherds are mostly Quartzose with two additional temper varieties defined by the presence of soil (Quartzose-Soil ) and carbonate ( Quartzose-Carbonate ) debris. The Mustique and Barbados temper compositions directly reflect island geology, implying that the temper and pottery were produced locally with no evidence for imported ceramics. In contrast, pottery from Union exhibits compositions that overlap with those of Carriacou, suggesting that Union may have been the source for some of the pottery on Carriacou, an island where pottery is thought to have been largely imported. This research is the first petrographic analysis of prehistoric pottery from Union and Mustique, and one of the most comprehensive mineralogical studies of Pre-Columbian ceramics in the Caribbean region. Highlights: Petrographic analysis of 93 sherds from several islands in the Lesser Antilles Not all temper groups successfully linked to island sources. Pottery likely transported to Carriacou whereas may be indigenous elsewhere.